High-accuracy measurements of core-excited transitions in light Li-like ions - Togawa, Moto; Kühn, Steffen; Shah, Chintan; Zaytsev, Vladimir A.; Oreshkina, Natalia S.; Buck, Jens; Bernitt, Sonja; Steinbrügge, René; Seltmann, Jörn; Hoesch, Moritz; Keitel, Christoph H.; Pfeifer, Thomas; et al. (Physical review, 2024)
The transition energies of the two 1⁢𝑠 core-excited soft x-ray lines (dubbed 𝑞 and 𝑟) from 1⁢𝑠2⁢2⁢𝑠⁢1⁢𝑆1/2 to the respective upper levels 1⁢𝑠⁢(2𝑆)⁢2⁢𝑠⁢2⁢𝑝⁢(3𝑃)⁢2⁢𝑃3/2 and 2⁢𝑃1/2 of Li-like oxygen, fluorine, and neon were measured and calibrated using several nearby transitions of He-like ions. The major remaining source of energy uncertainties in monochromators, the periodic fluctuations produced by imperfect angular encoder calibration, is addressed by a simultaneously running photoelectron spectroscopy measurement. This leads to an improved energy determination of 5 parts per million, showing fair agreement with previous theories as well as with our own, involving a complete treatment of the autoionizing states studied here. Our experimental results translate to an uncertainty of only 1.6 km/s for the oxygen line 𝑞⁢𝑟 blend used to determine the outflow velocities of active galactic nuclei, ten times smaller than previously possible.
Gesehen am 10.03.2025